Electronis Discussion
0 votes
16 views

In the circuit shown in the figure, if $C=0$, the expression for $Y$ is

  1. $Y=A \overline{B} + \overline{A}B$
  2. $Y=A+B$
  3. $Y=\overline{A} + \overline{B}$
  4. $Y=A \: B$
in Digital Circuits by (15.8k points)
recategorized by | 16 views

Please log in or register to answer this question.

Answer:
Welcome to GO Electronics, where you can ask questions and receive answers from other members of the community.
1,174 questions
78 answers
11 comments
43,916 users